Analisis Dampak Kehadiran Layanan Go-food terhadap Pendapatan dan Laba Usaha Mikro Kecil Menengah (UMKM) di Pramuka - Brillian Maulidanto; Ika Chandriyanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine and describe the impact of the presence of Go-food services on the income and profit of culinary MSMEs in Pemurus luar. The respondents of this study were MSME culinary entrepreneurs with data collection techniques through questionnaires, observation and documentation. The data analysis technique used was the Mann Whitney test,a test to see the difference in the median of the two groups. if the data is interval or ratio, then the distribution is not normal. The results of this study are Go-food has a major effect on the income and profit of culinary MSMEs in the field of snacks and heavy meals.